2022
DOI: 10.1128/spectrum.01626-22
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Gut Microbiota of Rats in High-Altitude Hypoxic Environments

Abstract: In this study, we investigated the effects of high-altitude hypoxic environments with low oxygen levels on the gut microbiota characteristics of rats. We observed that high-altitude hypoxia is an important environmental factor that can affect gut microbiota structure and diversity, thereby affecting homeostasis in the host intestinal environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A high-fat diet impairs mitochondrial oxygen uptake into host enterocytes, allowing facultative anaerobes such as the pathobiont Escherichia Coli to take over, resulting in an increase in the amount of choline catabolized into the precursor for TMAO [54]. The relative abundance of anaerobic bacteria has been reported to be significantly increased in the hypoxic groups [55]. The production of TMAO might be increased by combining hypoxia and microbial pathways, which in turn, lower HDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…A high-fat diet impairs mitochondrial oxygen uptake into host enterocytes, allowing facultative anaerobes such as the pathobiont Escherichia Coli to take over, resulting in an increase in the amount of choline catabolized into the precursor for TMAO [54]. The relative abundance of anaerobic bacteria has been reported to be significantly increased in the hypoxic groups [55]. The production of TMAO might be increased by combining hypoxia and microbial pathways, which in turn, lower HDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments have found that mice exposed to an altitude of 5,000 m for 30 days and that exposure to high-altitude and low-oxygen environments did not change the relative abundance of aerobic, anaerobic, facultative anaerobic, potentially pathogenic Gram-negative bacteria, and Gram-positive bacteria in mice, but significantly reduced the relative abundance of Epsilonproteobacteria, Actinobacteria, Clostridia, and Spirochaetes, and increased the relative abundance of Verrucomicrobia, indicating that exposure to low oxygen and high altitude may affect the composition of intestinal microbiota ( Zhang et al, 2018 ). In studies involving Wistar rats, it was observed that acute exposure to an altitude of 4,100 m resulted in a notable increase in the abundance of the Bacteroides genus, accompanied by a decrease in the abundance of the Prevotella genus, compared to the control group at sea level ( Bai et al, 2022 ). This phenomenon indicates a potential adaptation of the intestinal microbiota to high-altitude environments through alterations in microbial composition.…”
Section: The Changes In Intestinal Microbiota After Exposure To High-...mentioning
confidence: 99%
“…Additionally, rats exposed to low pressure (429 mmHg) for 7 days exhibited a significant increase in the abundance of aerobic and facultative anaerobic bacteria in fecal samples, while the abundance of anaerobic bacteria significantly decreased. This indicates that atmospheric pressure is an important exogenous factor regulating the composition of intestinal microbiota ( Bai et al, 2022 ).…”
Section: The Changes In Intestinal Microbiota After Exposure To High-...mentioning
confidence: 99%
See 2 more Smart Citations